Towards a new approach for coastal governance with an assessment of the Plettenberg Bay shore-based linefishery - King, Claire Margaret (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2006)
The overall aim of this thesis, as required by the funders, was to provide research that would contribute towards the development of a bay management plan, specifically information on the local fisheries. The thesis therefore includes an assessment of the local shore-based linefishery in terms of catch and effort and socio-economics, and the development of indicators from this information with which to assess the sustainability of the fishery. Finally an implementation strategy for an integrated coastal management approach for local resource governance is proposed The shore-based linefishery of Plettenberg Bay was assessed through a combination of roving creel and access point surveys which included questions aimed at the quantification of total effort, total catch and cpue, as well as the spatial trends in catch and effort. Angler demographics as well as opinions and knowledge of current fisheries regulations were obtained and the efficiency of the fishery inspectorate was assessed. The survey period extended from August 2003 to September 2004 during which 1189 angler interviews were conducted. Catch data obtained during this study was compared to catch data gathered during a research tagging program conducted in an area closed to fishing (Tsitsikamma National Park) and a semi-open area (Rebelsrus "“ Cape St. Francis), thereby highlighting differences in species composition, abundance and size distribution of certain species between areas of differing fishing pressures. The fishery surveys revealed that the shore-based fishery is primarily recreational (99%) and dominated by white males. Most anglers agreed with the current fisheries regulations (60%) and admitted to abiding by them, however when tested on the regulations of their target species, their knowledge was poor. Effort in the fishery was highly seasonal with peaks coinciding with major school holidays. Total annual effort was estimated at 102 566 angler-hours, with distinct spatial patterns in effort. Total annual catch for the Plettenberg Bay shore-based linefishery was estimated at 31 217 fish.yearâ »Â¹ with a total mass of 13.6 tons. Thirty-six fish species (26 teleost species and 10 elasmobranchs species) were identified during the survey period with Blacktail Diplodus capensis, Strepie Sarpa salpa, Red tjor-tjor Pagellus natalensis, Shad Pomatomus saltatrix and Sand steenbras Lithognathus mormyrus being the five most commonly caught species. Only 32% of interviewed anglers were successful in catching a fish with just 22% catching their primary target species. In addition, a large proportion of the anglers (69%) reported a decline in catch rate, with most blaming the commercial sector as a reason for the decline. The overall catch rate was (cpue) 0.374 fish.angler.hourâ »Â¹ or 170 grams.angler.hourâ »Â¹, considerably lower than that obtained from the fishery exempt area (TNP = 1. 02 fish.angler.hourâ »Â¹) and the partially exploited area (Rebelsrus = 0.91 fish.angler.hourâ »Â¹). In terms of species composition the most obvious difference between the three areas was the low proportion of non-migratory reef-associated species like red roman, poenskop, John brown, santer and bronze bream in Plettenberg Bay. Size comparisons revealed that the majority of species (particularly reef-associated species) were larger in the TNP than both the semi-exploited (Rebelsrus) and exploited area (Plettenberg Bay). Collectively theses findings suggest that certain species have been locally depleted, that recreational fishing has impacted heavily on the fish stocks and that even partial closure or limited access to an area can offer protection. From the results key issues were identified and sustainability indicators proposed according to the three sustainability domains (ecological, institutional and social) proposed by Pajak (2000). Within the ecological domain the most pertinent issue was the low catch rate, particularly for reef-associated species. Indicators to track these issues included: percentage of successful trips (where fish were caught), percentage of anglers that reached their daily bag limits and the proportion of the overall catch that comprised larger, more desirable species. Institutionally the most pertinent issue was the apparent inability of management institutions to manage effectively marine resources within Plettenberg Bay. Indicators within this domain included the proportion of anglers who were inspected, the existence of a localised management plan and an associated monitoring programme. Socially the fishery proved to be fairly sustainable. Indicators included in this domain were the proportion of subsistence anglers in the local fishing community, the percentage of correct answers pertaining to current fishery regulations, the level of noncompliance and the percentage of undersize fish retained. Aggregation of all the indicators within a sustainability matrix revealed that the Plettenberg Bay shore-based linefishery was unsustainable and thus requires increased local management effort. Since there is no local management strategy in place, an integrated coastal management approach for the governance of the coastal resources in Plettenberg Bay has been proposed. The development of a Coastal Management Plan and a subsidiary Bay Management Plan provide the frameworks within which management strategies can be put into operation.
Keywords: Fishery management -- South Africa -- Plettenberg Bay; Fisheries -- South Africa -- Plettenberg Bay; Coastal zone management -- South Africa -- Plettenberg Bay